Variables that predict the satisfaction and motivation of the directors of educational organizations - Falcón Armas, Andrés; Díaz Vilela, Luis (Avances en Supervisión Educativa, 2007)
This article analyzes the job of school head teacher in public educational centres with four main objectives: a) to better understand what variables predict and explain their occupants' behaviour; b) to analyze which organizational climate variables have an influence on several personal and organizational outcomes; c) to get a first hand information about the motives leading teachers to apply to, or refuse, the job; and d) to propose some directions on the job redesign. We developed this research Within the framework of the Job Characteristics Model (Hackman & Oldham, 1980), focusing on the implications of a good job-person fit.Using the JDS questionnaire, an organizational climate questionnaire, and a job acceptance/rejection motives scales, we draw data from 932 educational workers of which 350 were head teachers. Several descriptive results are depicted which may help to understand how are the head teachers experiencing their job and what are the differences between the target sample and other educational professionals. We also applied several regression analyses that give some light on the predictors of general satisfaction, internal motivation, and growth need strength.Our conclusions yield to some orientations to find a better job-occupant fit, and to improve organizational climate in the educational public administration as the core source of outside school stimulation.
Keywords: work design; school head teacher job; job analysis and intrinsic motivation; organizational climate